2023
DOI: 10.3390/plants12183203
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Mulching Film vs. Traditional Polyethylene: Effects on Yield and Quality of San Marzano Tomato Fruits

Ida Di Mola,
Eugenio Cozzolino,
Lucia Ottaiano
et al.

Abstract: Mulching is a common practice for improving crop yield and obtaining an out-of-season production, but when made using plastic materials it can bring environmental problems due to the management and the disposal of films at the end of the cropping seasons. To increase the sustainability of this practice, recently, mulching films made with biodegradable organic materials have become more widely used. Our aim was to evaluate the effect of a biodegradable mulching film on yield and qualitative traits of the San Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
5
1
Order By: Relevance
“…In our research, both antioxidant activities were affected by the combined effect of the environment and mulching film. In particular, we highlighted a contrasting response of HAA to biodegradable mulching, contrary to previous studies on tomatoes [17,54] and strawberries [6], which report a positive influence of biodegradable films on hydrophilic antioxidant activity. In fact, only in Sicily, the experimental Materbi ® obtained a high level of HAA, while the other biodegradable film in Sicily and both films in Campania showed lower values.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our research, both antioxidant activities were affected by the combined effect of the environment and mulching film. In particular, we highlighted a contrasting response of HAA to biodegradable mulching, contrary to previous studies on tomatoes [17,54] and strawberries [6], which report a positive influence of biodegradable films on hydrophilic antioxidant activity. In fact, only in Sicily, the experimental Materbi ® obtained a high level of HAA, while the other biodegradable film in Sicily and both films in Campania showed lower values.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies reported similar findings for biodegradable mulching. Di Mola et al [17], in an openfield trial on processing tomatoes with two different biodegradable mulches (including MaterBi ® ), obtained higher marketable yields compared to the non-mulched soil. Cozzolino et al [19] also obtained higher yields and number of fruits when melons were cultivated on MaterBi ® films compared to cultivation on LDPE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turoni srl, Forlì, Italy) equipped with an 8 mm diameter probe. Space parameters, a* (−a, green/red, +a) and b* (−b, blue/yellow, +b) responses, were detected on the two opposite sides of each fruit, as well as the firmness measurements [58]; color data were shown as red/yellow (a/b) ratio [58].…”
Section: Plant Materials Experimental Treatments Crop Management Samp...mentioning
confidence: 98%
“…However, since different colored plastic films still provide inconclusive results, they need to be tested in interaction with site-specific factors, such as crop season, soil, and crop types. Mulching of tomato crops has been deeply investigated [53][54][55][56][57][58], but very few studies were conducted on the effect of yellow and silver mulching films on yield and fruit quality traits [51,59].…”
Section: Introductionmentioning
confidence: 99%